PENGARUH PEMBERIAN EKSTRAK IKAN GABUS TERHADAP PENINGKATAN KADAR ALBUMIN DARAH PADA PENDERITA DIABETES MELLITUS DENGAN GANGREN - Eny Sayuningsih; Ani Intiyati; Bambang Giatno R (Poltekkes Kemenkes Surabaya, 2014)
This research is analytical research, with Quasy experimental design, pre and post test design, which aims to study the effect of fish extract cork on blood albumin levels in patients with diabetes mellitus with gangrene. As the population are all people with Diabetes Mellitus with gangreen, while the samples were divided into three groups: treatment group 1 were given extracts of catfish as much as 2 x 35 cc/day for 12 days (EIG1), then the 2 treatment groups given catfish extract as much as 1 x35 cc/day for 12 days (EIG2) and the control group were given a lacebo . Hash Research shows the average blood albumin levels in group 1 (EIG1 2 x 35 cc/day) before and after treatment had a significant difference (p = 0.000) with an average pre- treatment amounted to 2.38 ± 0.66 g/dl and after treatment was 2.73±0.36 , which means an increase of 0.35 g/dl. In group 2 (EIG2 1 x 35cc/hari) average blood albumin levels before and after treatment had a significant difference (p = 0.001) with an average pre- treatment to 2.57±0.19 g/dl and after treatment was 2.87±0.21 which means an increase of 0.32 g/dI . While the use of the placebo group 3, the average blood albumin levels before and after treatment did not have significant difference (p=0.797) with an average pre- treatment by 2.63±0.36 g/dl and after treatment was 2,63±0.37, which means there is an increase. The results of ANOVA test result that the average levels of albumin across the groups at baseline (before treatment) had no difference (p=0.9930.05). While that seen after treatment and the difference in the average levels of albumin across the group has significant difference (p=0.0000.05). It can be concluded that the extract of fish cork has been shown to increase blood albumin levels were statistically significant with the administration of 2 bottles per day @ 35 cc. Keywords: Diabetes Mellitus, albumin levels, Extract, Fish Cork